3D printing with 2D colloids: designing rheology protocols to predict 'printability' of soft-materials. Issue 6 (22nd January 2019) - Corker, Andrew; Ng, Henry C.-H.; Poole, Robert J.; García-Tuñón, Esther
Abstract : Delving into the ' printability ' of soft matter using bespoke rheological protocols on suspensions and gels of 2D colloids. Abstract : Additive manufacturing (AM) techniques and so-called 2D materials have undergone an explosive growth in the past decade. The former opens multiple possibilities in the manufacturing of multifunctional complex structures, and the latter on a wide range of applications from energy to water purification. Extrusion-based 3D printing, also known as Direct Ink Writing (DIW), robocasting, and often simply 3D printing, provides a unique approach to introduce advanced and high-added-value materials with limited availability into lab-scale manufacturing. On the other hand, 2D colloids of graphene oxide (GO) exhibit a fascinating rheology and can aid the processing of different materials to develop 'printable' formulations. This work provides an in-depth rheological study of GO suspensions with a wide range of behaviours from Newtonian-like to viscoelastic 'printable' soft solids. The combination of extensional and shear rheology reveals the network formation process as GO concentration increases from <0.1 vol% to 3 vol%. Our results also demonstrate that the quantification of 'printability' can be based on three rheology parameters: the stiffness of the network via the storage modulus ( G ′), the solid-to-liquid transition or flow stress ( σ f ), and the flow transition index, which relates the flow and yield stresses (FTI = σ f / σ y ).